Factors related to sweet consumption of Bangyai CUP health care workers. - ศิริอนันต์ ปูรณินท์ (Thai Dental Public Health Journal, 2008)
This study aimed to investigate the knowledge attitude and practice that related to sweet consumption. The outcome of this study would be used to improve health care worker behavior shaping program. The target group consisted of 209 staffs who worked in Bangyai hospital and in health centers in Bangyai contracting unit for primary care (CUP) network. The questionnaire was tested for validity and reliability. Frequency, percentage, mean, standard deviation, Chi-square, and logistic regression were used to analyze data. The result revealed that 55.5% of the target group had moderate knowledge. 56% had good attitude towards decreasing sweet consumption program. 71.8% could practice moderately. The relationship study revealed that the factors that related significantly (p<0.05) were age, gender, marital status, childbearing, educational level, work experience, and attitude which related to behavior. The factors that did not related significantly were systemic disease, BMI (Body Mass Index), type of work, place of work, and knowledge about sweet consumption. There was no factor that significantly influenced sweet consumption behavior.